Misja EULEX Kosowo - Izydorczyk, Monika; Oblińska, Kornela (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The European Union made the decision to launch the EULEX Kosovo mission on February 4, 2008. Its mandate was envisaged for 28 months from the approval of the Operation Plan (OPLAN), i.e. from February 16, 2008. As scheduled, the mission commenced on June 15, 2008, yet it failed to take over the responsibility for the tasks from the UNMIK mission of the United Nations. Owing to delays, the EULEX Kosovo mission achieved initial operational capability on December 9, 2009 and became fully operative on April 6, 2009. EULEX Kosovo is the largest mission ever launched under the Common Security and Defence Policy (CSDP). The mission’s status has aroused serious controversies as out of 27 EU member states, Greece, Slovakia, Spain, Romania and Cyprus have not recognized Kosovo as an independent state. As an organization, the European Union officially refers to the province as “Kosovo – under UN Security Council Resolution 1244.” Since EULEX Kosovo remains operational and is an ‘open’ mission it is difficult to unanimously assess the efficiency of its operation. The mission has been operating under complicated political circumstances which result from the fact that Kosovo’s independence has been approved by some of the EU states.